2010
DOI: 10.1152/ajpheart.00040.2009
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic deformation characteristics of porcine aortic valve leaflet under normal and hypertensive conditions

Abstract: Calcific aortic valve (AV) disease has a high prevalence in the United States, and hypertension is correlated to early onset of the disease. The cause of the disease is poorly understood, although biological and remodeling responses to mechanical forces, such as membrane tension, have been hypothesized to play a role. The mechanical behavior of the native AV has, therefore, been the focus of many recent studies. In the present study, the dynamic deformation characteristics of the AV leaflet and the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 31 publications
(35 reference statements)
4
65
2
Order By: Relevance
“…Mechanical stresses are oriented circumferentially in the healthy valve and are altered from increased hemodynamic pressures or aberrant deformations due to altered wall stresses during the contractile cycle during ischemic cardiomyopathy. These altered stresses typically manifest as altered strains (1,12,13,27). In an attempt to mimic this cell microenvironment in a simplified model, we engineered 2D lamellae of primary ovine VECs by seeding the cells on micropatterned (28) deformable elastomeric substrates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical stresses are oriented circumferentially in the healthy valve and are altered from increased hemodynamic pressures or aberrant deformations due to altered wall stresses during the contractile cycle during ischemic cardiomyopathy. These altered stresses typically manifest as altered strains (1,12,13,27). In an attempt to mimic this cell microenvironment in a simplified model, we engineered 2D lamellae of primary ovine VECs by seeding the cells on micropatterned (28) deformable elastomeric substrates.…”
Section: Resultsmentioning
confidence: 99%
“…VEC monolayers were subject to 0% (control), 10%, or 20% uniaxial cyclic strain at 1 Hz for 24 or 48 h using a custom-built cyclic stretcher device (Movies S1 and S2). The latter two strain magnitudes are representative of low-or high-strain regimes in mammalian cardiac valves (27,57). Cyclic strain was either applied parallel (termed "anisotropic") or orthogonal (termed "anisotropic-orthogonal") to initial tissue alignment, simulating healthy or diseased valves (12,13).…”
Section: Methodsmentioning
confidence: 99%
“…A regular array of tissue dye markers with a 1 mm grid spacing was applied using tissue marking dye (Black Shandon Tissue Marking Dye, Thermoelectron Corporation, Pittsburgh, PA, USA) to the aortic surface of the leaflets using a template placed behind the leaflet as reference (figure 1a,b). Valves were deployed into two aortic annulus models: a circular control annulus (22 figure 1c,d ), representative of highly eccentric explanted and in vivo TAVRs from CT imaging [5,6]. Both circular and eccentric orifices were constructed such that the cross-sectional orifice areas were the same.…”
Section: Valve and Aortic Root Modelmentioning
confidence: 99%
“…They also compared their valve explant experimental results with shear stresses calculated for in vivo measurements using their theoretical model and found that they were similar (ie, 77-92 dynes/cm 2 on the ventricular side). In addition, Yap et al 77 found that hypertension increases the stretch of the valve tissue in both the radial and circumferential directions. Severe hypertension caused an even higher degree of valve stretch.…”
Section: Hemodynamic Effects On Aortic Valve Tissuementioning
confidence: 99%
“…96 However, when pathological blood flow exposes the endothelium to disturbed, low-shear-stress flow on the aortic side, endothelial dysfunction can occur, leading to inflammation, enhanced permeability of small molecules through the EC barrier, and potentially apoptosis of the ECs (Figure 3). 1,77,97,98 The increase in endothelial permeability results in nonspecific regulation of the diffusion of molecules into the tissue such as inflammatory cytokines 97 that may lead to propagation of the myofibroblast phenotype of VICs and disease progression. In addition, EC apoptosis would reduce expression and diffusion of protective paracrine signaling molecules (eg, NO and CNP), which results in less regulation of the activated myofibroblast phenotype.…”
Section: Hemodynamic Effects On Aortic Valvular Ecsmentioning
confidence: 99%